CH Alkenylations with Alkenyl Acetates, Phosphates, Carbonates, and Carbamates by Cobalt Catalysis at 23 °C1. Issue 21 (13th April 2015) - Moselage, Marc; Sauermann, Nicolas; Richter, Sven C.; Ackermann, Lutz
Abstract Inexpensive cobalt catalysts with N‐heterocyclic carbene ligands enable direct arene alkenylations with easily accessible alkenyl acetates through regioselective CH/CO functionalizations in a stereoconvergent fashion. The versatile cobalt catalyst was broadly applicable and thus also allowed for the efficient conversion of alkenyl phosphates, carbonates, and carbamates at ambient temperature.